Different energy and protein ratio in feed formulation of village chicken based on alternative feedstuffs under two management systems - Norazaman, Nadia Ezdianie (2016)
Energy and protein are two important components of food that generates a lot of interest and challenges to nutritionists. Energy and protein ration play important role in formulate the diet of the poultry. It is important to find alternative to replace the uses of imported grains (plant proteins) in the feed of chickens with local sources to reduce the production cost in poultry production. This research aim to determine the effect of dietary protein and energy level on growth performance, carcass characteristic and meat quality of Arabian strain village chicken raised in close confinement and free range system and fed on dehydrated food waste (DFW), dehydrated superworms (DSW) and dried eggs (DE). DFW as the main energy source, DSW and DE as the main protein sources. This research divided by two experiment of feeding trial (starter and grower phase). The chicks were reared in cages from day one old till the age of 6 weeks. During week 7 until week 12 the chicks were randomly allocated to two production system (indoor pen and free range system). The growth performance of the chicks was measured weekly. Six experimental diets were formulated to have 3 level of energy to protein ratio (EP134, EP150 and EP164). Every ratio has two different protein sources with the same value of inclusion. T1 EP150 (DFW+Fishmeal) as a control, T2 EP164 (DFW+DSW), T3 EP164 (DFW+DE),T4 EP150 (DFW+DSW+DE), T5 EP134 (DFW+DSW) and T6 EP134 (DFW+DE). Each treatment comprised of two replicates with fifteen birds each. Feed and water were provided ad libitum. A complete randomized design was used in experiment. Proximate analysis of the main ingredient in the diet showed DFW 4,500.54kcal/kg for gross energy and 25.18% of crude protein. Meanwhile DSW and DE have high in crude protein 46.54% and 46.33% respectively and DE have significantly higher (P<0.05) for protein quality to compared with DSW and this made it a suitable alternative source of protein. At the end of week 6, a single diet energy:protein (E:P) ratio of 134 kcal ME/kg protein supported optimum feed conversation ratio and growth rate of Arabian strain village chicken aged between one to six weeks. In experiment two, for feeding trial T6 showed the best performance among the other treatment but diet E:P ratio of 164 kcal ME/kg protein supported optimum growth performance during the grower stages. The production system with free range resulted in increased feed intake and poorer FCR compared with the indoor system. The indoor system had superior growth performance. There was no statistical interaction effect between management system and treatment on carcass characteristics of the village chickens. However, abdominal fat tended to decrease as dietary protein increased with the 134 ratio (P<0.05), while higher energy levels increased abdominal fat from 13.75g to 18.00g when energy was increased with the 164 and 150 ratio respectively. For the chemical composition of the breast muscle, the protein content of breast muscle ranged from 22.66 to 24.45, being significantly higher (p<0.05) in free range production system. Production system also showed high values for moisture and fat in indoor pen system. The present study shows high CP content with the ratio 134, 150 and 164 respectively. Fat content high with the ratio 164 with the highest energy in the treatment and the lowest fat content in the 134 ratio with lowest energy. The pH of free range chickens was lower than that of indoor pen system. Free range system chickens also have significantly different (P<0.05) presented with the highest value in drip loss, cooking loss, L*, a*, b* and the shear force. For the conclusion, the use of appropriate ratio in formulated the diet are very important in the growth performance, carcass characteristic and meat quality of Arabian village chicken. These by-products can be considered as an alternative source of protein-energy rich poultry feed. These findings have implications on ration formulation for village chicken in Malaysia. Free range system of village chicken seems to be a possible alternative to the conventional method (indoor pen system). This is due to the more natural rearing conditions that increase motor activity, favors the development of the muscle mass, reduce fatness and high with the protein and also contribute to animal welfare issues. Furthermore, this kind of production system is more practical and cheaper through using appropriate technology.